KARAKTERISTIK TAFSIR AL-IBRIZ: SEBUAH KAJIAN TERHADAP KARYA TAFSIR NUSANTARA KARYA K.H. BISRI MUSTOFA REMBANG - Karsidi; Muhith (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The study of Nusantara Qur’anic exegesis is essential for understanding how the Qur’an interacts with local socio cultural contexts. One significant work in this tradition is Tafsir Al-Ibriz by K.H. Bisri Mustofa of Rembang, which was written in Javanese Pegon and aimed at pesantren communities and the wider Javanese Muslim society. This study aims to analyze and describe the characteristics of Tafsir Al-Ibriz, particularly in terms of language usage, interpretive method, exegetical orientation, and da‘wah approach within the framework of Nusantara tafsir. This research employs a qualitative library research method using a descriptive analytical approach to examine the primary text and relevant secondary sources. The findings reveal that Tafsir Al-Ibriz is characterized by its use of accessible local language, an ijmali (concise) interpretive method, and a strong socio-religious orientation that emphasizes practical moral guidance. The study concludes that Tafsir Al-Ibriz represents an important contribution to Nusantara Qur’anic exegesis and plays a significant role in making Qur’anic teachings more comprehensible and relevant to local Muslim communities.